Legal Culture - López Medina, Rocío del Carmen (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
In the latest 40 years the notion of "legal culture" has taken the pride of place in different fields of study, as in legal sociology, jurisprudence, comparative legal studies. This is due to the necessity to connect the formal notion of legal system as a set of norms with the concrete activities of citizens and legal professionals in a social context. In this entry I try to identify some central features of the concept of legal culture considering the contributions of Lawrence M. Friedman and Giovanni Tarello.
Keywords: Legal culture; legal system; legal operators; interpretation; ideology